Evaluation of various beams using computational tools - Jayant, Bhagya; Meena, Rahul Kumar; Singh, Aastha; Mishra, Agyeya; Dalal, Navneet; Singh, Rajvir; Kumar, Shailendra; Raj, Ritu (AIP conference proceedings, 2023)
This study aims to demonstrate a Python-based model or Python scripts for static analysis of beams using force method for a set of beams with changing cross – sections categorized on the basis of types of beam structure and loading conditions. It aims to fill the gap of less research in the domain of static analysis of beams by formulating the beam analysis into an algorithm using the programming language, Python. The types of beam structures under consideration are cantilever, propped cantilever, simply supported, and fixed beam. And the loading conditions of point load and uniformly distributed load (UDL) are taken as per subject logic. The entire program has been prepared and verified by referring to standard books of Civil Engineering. Readers may run the provided Python script or code in any Python release for Windows and/or Pythonista. The research paper targets to simplify the concepts in this domain in a fast, an efficient, a user – friendly, and an accurate way. Fellow researchers working in a similar field of interest may utilize this paper as an aiding tool for their research and save their time and manual effort.